Water Exposure Time Distributions Controlled by Freshwater Releases in a Semi‐Enclosed Estuary - Caitlin R. R. Turner; Matthew Hiatt (Water Resources Research, 2025)
Abstract Freshwater diversions manage water shortages, salinity, and control floodwater by redirecting river flows; however, their full ecological and hydrological impact remains unknown. This study examines the Lake Pontchartrain Estuary in Louisiana using a hydrodynamic model and Lagrangian particle tracking to assess how diversion operations (open, closed) and tributary discharge levels (low, median, high) influence water exposure time—the cumulative duration water remains in a domain, including re‐entry. Exposure time was analyzed based on the time required for 50%, 75%, and 90% of released particles (E50, E75, and E90) to leave a defined region of interest (ROI). Results show that when the diversion is open, high tributary discharge reduces exposure times by 51% compared to low discharge. In contrast, when closed, tributary discharge has minimal effect. To identify zones vulnerable to poor water quality due to stagnant water, the spatial heterogeneity of exposure time was evaluated using two metrics: system‐wide (time water remains in a system) and localized (time water remains within a ROI) exposure times. The spatial distribution and magnitude of increased exposure times varied between metrics and tributary discharge, highlighting the complexity of transport dynamics. For example, low tributary discharge led to larger isolated zones with longer system‐wide and localized exposure times. High tributary discharge created direct flow paths of diversion‐sourced water through tidal inlets, short‐circuiting the system and creating flow separation. These findings establish a framework for identifying transport mechanisms that influence exposure time and highlighting areas that may be vulnerable to poor water quality.